1994
DOI: 10.1083/jcb.127.6.1703
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the chondroitin sulfate proteoglycan phosphacan, the extracellular domain of a receptor-type protein tyrosine phosphatase, with neurons, glia, and neural cell adhesion molecules.

Abstract: Abstract. Phosphacan is a chondroitin sulfate proteoglycan produced by glial cells in the central nervous system, and represents the extracellular domain of a receptor-type protein tyrosine phosphatase (RPTPg'/B). We previously demonstrated that soluble phosphacan inhibited the aggregation of microbeads coated with N-CAM or Ng-CAM, and have now found that soluble ~25I-phosphacan bound reversibly to these neural cell adhesion molecules, but not to a number of other cell surface and extracellular matrix proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
191
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(200 citation statements)
references
References 54 publications
6
191
0
3
Order By: Relevance
“…44 The carbonic anhydrase domain interacts with the cell recognition molecule contactin, 51 whereas the spacer region can interact with several other cell adhesion molecules including NrCAM, L1CAM, NCAM, contactin-1 and contactin-2/TAG-1. [52][53][54][55][56] PTPRZ1 gene products are expressed from early developmental to adulthood in glial cells 47,[57][58][59] as well as in certain population of neurons [60][61][62][63] and are implicated in neuron-glial cell interactions that involve on bi-directional signaling, including myelination and node of Ranvier formation, through interactions with neuronal cell adhesion molecules. 55,56 Interestingly, in situ hybridization analysis has shown that PTPRZ1 is expressed in the subventricular zone of the lateral ventricles in early embryos and in adults, in the subgranular zone in the dentate gyrus of the hippocampus of adults, 57,64 and in adult glial progenitor cells, 65 suggesting that PTPRZ1 also has a function in adult stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…44 The carbonic anhydrase domain interacts with the cell recognition molecule contactin, 51 whereas the spacer region can interact with several other cell adhesion molecules including NrCAM, L1CAM, NCAM, contactin-1 and contactin-2/TAG-1. [52][53][54][55][56] PTPRZ1 gene products are expressed from early developmental to adulthood in glial cells 47,[57][58][59] as well as in certain population of neurons [60][61][62][63] and are implicated in neuron-glial cell interactions that involve on bi-directional signaling, including myelination and node of Ranvier formation, through interactions with neuronal cell adhesion molecules. 55,56 Interestingly, in situ hybridization analysis has shown that PTPRZ1 is expressed in the subventricular zone of the lateral ventricles in early embryos and in adults, in the subgranular zone in the dentate gyrus of the hippocampus of adults, 57,64 and in adult glial progenitor cells, 65 suggesting that PTPRZ1 also has a function in adult stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of phosphacan on C6 cell adhesion to tenascin-C are similar to the previously observed inhibition of neuronal adhesion to the neural cell adhesion molecule Ng-CAM/L1. It was concluded from these studies that inhibition of neuronal adhesion by both neurocan and phosphacan (which bind to Ng-CAM/ L1) is mediated by direct effects on the cells rather than via binding to the substrate, since the proteoglycans also inhibited adhesion to a substrate consisting of anti-Ng-CAM antibodies, to which the proteoglycans do not bind (9,10). Phosphacan also inhibited the adhesion of C6 cells to Ng-CAM (7) but not to laminin (1).…”
Section: Discussionmentioning
confidence: 99%
“…Binding assays were performed as described previously (10). Briefly, proteins at a concentration of 1-12 nM were coated in removable Immulon-4 wells, and binding of 125 I-labeled neurocan and phosphacan was measured in 20 mM Tris, pH 7.4, containing 150 mM NaCl, 2 mM CaCl 2, 2 mM MgCl 2, 0.02% NaN 3 , and 1 mg/ml heat-treated BSA, following incubation with gentle shaking (45 rpm) for 9 -12 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been found that aggrecan affects laminin activity on neuron cell body substratum attachment depending on the order in which the two molecules are adsorbed, providing evidence that the effect of aggrecan is not simply additive [132]. It has thus been suggested that aggrecan and other CSPGs may exert their inhibitory effect by adversely changing the activity of laminin and other growth promoting molecules through protein-protein interactions and conformational changes.Interactions between proteoglycans and laminins have been elucidated including CSPG direct binding to and masking of laminin integrin sites [133][134][135]. It has also been found that certain CSPGs appear to affect only particular growth promoting molecules.…”
mentioning
confidence: 99%